ROBERT A. HUMPHREYS: Liberation in South America 1806-1827. The Career of James Paroissien . University of London. The Athlone Press, 1952. Londres. 177 págs. ilustracs. y mapas. - Nieto Vélez S.J., Armando (1953)
No contiene resumen